Measuring and Modelling Crescent Image Contrast with a DSLR Camera - M. Hasan Faadillah; Mahasena Putra (University of Muhammadiyah Sumatera Utara, 2023)
The Hijri calendar is synonymous with hilal (young crescent moon) observation. Nowadays, hilal observation is expanding to various circles using instruments that are easily obtained and widely available on the market. The configuration that is often chosen uses a portable telescope and DSLR camera to produce images. Several theoretical models on the visibility of celestial objects at twilight, including the crescent moon, have been developed by several researchers. This has prompted the study of crescent image contrast and testing of more and more data. This study contains alternative processing of crescent moon images from DSLR cameras to measure the contrast value of observations ( 16Cobs